Le numérique au secours des monnaies locales et complémentaires - Bénédicte Martin (Netcom)
Local and complementary Currencies as well as crypto currencies appear after the 2008 crisis and are built on a critique of the dominant financial system. However, these two types of alternative currencies are based on different society projects and radically different values. While Decentralized virtual currencies are speculative and rely on an anonymous community, Local and Complementary currencies which aim to enhance citizens community participation through transactions purposes take root in their territories. They serve the project of a common citizen currency by empowering local producers to build up their region’s resilience. Therefore this territory project move beyond the notion of administrative boundaries to give shape to new territories frontiers in terms of social, solidarity and environmental values. However the challenge for these local currencies is to meet up fully with common re-defined territory identities and to transcend the militant movement by adopting new digital means to facilitate their use.